Transportation engineering: Kỹ thuật giao thông - Ngo Tri Thuong (Trường Đại học Thuỷ Lợi, 2021)
Contents: Chapter 1: The profession of transportation; Chapter 2: Transportation system and organization; Chapter 6: Fundamental principle of traffic flow; Chapter 9: Capacity and level of service; Chapter 12: forecasting travel demand; Chapter 15: geometric design (GD); Chapter 17: Soil engineer for highway construction; Chapter 19: Flexible pavement; Chapter 20: rigid pavement (RP)